Species-Related Differences in the Properties of Receptor-Operated TRPC4 Channels in Intestinal Myocytes of Rodents - Dryn, D.O.; Gryshchenko, A.V.; Bolton, T.B.; Zhu, M.X.; Zholos, A.V. (Нейрофизиология, 2016)
TRPC4 proteins form receptor-operated cation channels that are activated in synergy by M₂ and M₃ acetylcholine (ACh) receptors coupled to Gq/11 and Gi/o proteins, respectively. These channels are widely expressed in the brain and smooth muscles where they perform a number of important functions, including control of GABA release from the dendrites and cholinergic excitation of smooth muscles. The biophysical properties of TRPC4 currents directly activated by GTPγS in mouse cells remain mostly unknown. We, thus, aimed to investigate these channels in mouse ileal myocytes where a prominent TRPC4-mediated cation current termed mICAT is observed, and to compare the behavior of this current with that of the better studied mICAT in guinea-pig myocytes. Although the respective cation current responses to carbachol (CCh) at –50 mV (i.e., at the value close to the normal resting potential in these cells) were highly similar, mICAT in the mouse lacked the permissive action of intracellular Ca2+ on channel opening. The slope factor of the muscarinic cation conductance, which is a defining property of voltage-dependent behavior, was identical in both species. There were differences in the potential at which the current peaked at negative potentials, but not in the maximal current densities. Major differences were found in the kinetics of mICAT voltage-dependent relaxations, which were much faster in the mouse. The above rodent species employ two different strategies for the open probability increase by activated G-proteins; the mean open time was shorter in the mouse compared to that in the guinea-pig (15.1 ± 5.2 msec, n = 8, vs. 80.0 ± ± 19.7 msec, n = 9; P < 0.01). Correspondingly, the instantaneous frequency of channel opening was much higher in the mouse (154.1 ± 18.8 sec⁻¹ vs. 70.2 ± 7.3 sec⁻¹ in the guinea-pig; P < 0.001). These functional differences are based on the differences found in the corresponding TRPC4 amino acid sequences of the two rodent species, which are mainly clustered in the cytosolic C-terminus of TRPC4 protein. Keywords: muscarinic receptors, receptor-o